2015
DOI: 10.14310/horm.2002.1604
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an AVP-NPII mutation within the AVP moiety in a family with neurohypophyseal diabetes insipidus: review of the literature

Abstract: Familial neurohypophyseal diabetes insipidus (FNDI) is a disorder characterized by excess excretion of diluted urine (polyuria) and increased uptake of fluids (polydipsia).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…The present study defines clinical and molecular characteristics of 22 affected patients with familial central DI from 13 different Italian families. Eight of the identified mutations were known to be associated with adNDI of the AVP-NPII gene and have previously been reported by others (8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,34,35,36,37,38,39), while two novel mutations are here described for the first time. Genetic analyses revealed that all affected members were heterozygous for the mutations as expected from autosomal dominant mode of inheritance.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The present study defines clinical and molecular characteristics of 22 affected patients with familial central DI from 13 different Italian families. Eight of the identified mutations were known to be associated with adNDI of the AVP-NPII gene and have previously been reported by others (8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,34,35,36,37,38,39), while two novel mutations are here described for the first time. Genetic analyses revealed that all affected members were heterozygous for the mutations as expected from autosomal dominant mode of inheritance.…”
Section: Discussionmentioning
confidence: 53%
“…More than 70 disease-causing mutations resulting in a defective pro-hormone and a deficiency of AVP have been described in adNDI (8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30). The AVP-NPII gene consists of three exons where exon 1 encodes the signal peptide, the AVP peptide and the first nine amino acids of NPII; exon 2 encodes the majority of NPII and exon 3 encodes the carboxyl-terminal 17 amino acids of NPII and copeptin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Он на-ходится на 20-й хромосоме у человека (в 13-й позиции, от 3 082 554 до 3 093 520 пары оснований), 7-й хромосоме у крысы и 2-й хромосоме у мыши (пары оснований от 130 580 620 до 130 582 554) (http://www.ncbi.nlm.nih.gov/ gene). Этот ген состоит из 3 экзонов и 2 интронов, коди-рующих сигнальный пептид (19 аминокислот в первом эк-зоне); гормон AVP (9 аминокислот также в первом экзоне); нейрофизин 2 (NP2, 93 аминокислоты), кодируемый всеми тремя экзонами, и C-концевой гликопептид копептин (39 аминокислот в третьем экзоне) в перечисленном порядке (Iwasaki et al, 2000, Koufaris et al, 2015. Особенностью мРНК avp является наличие 3ʹ-поли(А) конца, который регулируется в зависимости от осмотических проблем и, как известно, повышает эффективность трансляции и увеличивает стабильность этой мРНК (Carrazana et al, 1988).…”
Section: ген вазопрессина и его известные естественные вариантыunclassified
“…Крысы Браттлборо имеют рецессивную аутосомную мутацию, в то время как семейные нейрогипофизарные DI человека почти всегда наследуются по аутосомно-доминантному типу, и лишь только несколько семей с этой патологией демонстрируют ее аутосомно-рецессивный тип наследования (Koufaris et al, 2015). В гене avp было описано по крайней мере 60 мутаций, способных вызвать у человека нейрогипофизар-ную форму DI.…”
Section: ген вазопрессина и его известные естественные вариантыunclassified